Living dangerously in a virus world: are we at the losing end? - Sekawi, Zamberi (Universiti Putra Malaysia Press, 2018)
Infectious diseases still contribute to significant morbidity and mortality in many countries around the world, which includes Malaysia. Human viruses are among the important causative pathogens that pose serious threats to the world population. It has been demonstrated in over the past centuries that viruses can kill millions through outbreaks, especially infections that involve the respiratory system, such as the influenza pandemic and SARS coronavirus outbreak. These kinds of infections can spread rapidly across the world. Malaysia has had its fair share of fatal outbreaks such as the enterovirus 71 and Nipah virus outbreaks. Four important issues will be highlighted in this paper: the molecular epidemiology of respiratory viruses, prevention of the hand-foot and-mouth disease, beyond childhood hepatitis B immunisation and adult immunisation. Respiratory viruses are the cause of the most common infections among humans. The vast majority of the infections are asymptomatic and mild in nature, and they are also mostly self-limiting. Molecular methods offer increased sensitivity and specificity in detecting these respiratory viruses. Such methods can also be used to detect other uncommon but important viruses. Molecular epidemiology is a useful and increasingly valuable tool. It can be used to explain viral evolution, its geographical transmission and hospital infection transmission. From these data, we can design strategies and interventions to counteract and prevent infections. The use of single interfering RNA as an anti-RSV agent will also be highlighted. Hand-foot-and-mouth disease used to be a mild and self-limiting childhood disease, but in recent years an increasing number of deaths have been reported due to complications involving the central nervous system particularly involving the related enterovirus 71. This clearly shows that the virus has evolved and mutated and increased in pathogenicity. To counteract such infections, in addition to maintaining a high level of hygiene, an effective vaccine against the virus is also badly needed. The development of a vaccine for the enterovirus 71 will be highlighted, where it shows good potential, through the use of a combination of inter-buccal and intra-dermal routes, to achieve maximum protection. This combination was shown to elicit the production of both IgA and IgG. Further, the childhood hepatitis B immunisation program has been successful in reducing the prevalence of hepatitis B and hepatocellular carcinoma in Malaysia. However, beyond this childhood programme, we are now increasingly facing the issue of hepatitis B virus mutants and occult hepatitis B infections. This poses a threat of transmissions, particularly during blood transfusion and also organ transplants. What is worrying is that this condition has been found to occur more among vaccinees than unvaccinated individuals. The impact of these mutants and occult infections is also explored. Adult immunisation is thus of growing concern particularly because of its low uptake despite the availability of effective vaccines. Adults need to be vaccinated just like children as the effectiveness of childhood vaccines wanes with aging. Majority of adults, particularly the elderly, have increasing morbidity due to the onset of chronic diseases and thus it is vital for them to get themselves protected via immunisation. Health care professionals should also be immunised against specific diseases to protect themselves and to prevent transmission to their patients. Unfortunately, the uptake of such has been inconsistent, and thus strategies and interventions should be carried out to remedy the situation. We face constant threats from viral infections which have the potential to affect mankind adversely, as we have experienced before. It would therefore be prudent to be at the forefront in tackling these threats.